2017
DOI: 10.1002/jcb.26025
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1/miR‐181c Regulates Osteopontin (OPN)‐Mediated Synoviocyte Proliferation in Osteoarthritis

Abstract: Osteoarthritis (OA) is characterized by progressive destruction of articular cartilage, resulting in significant disability. Inflammatory cytokines commonly initiate the extreme changes in the synovium and cartilage microenvironment of the OA patients, subsequently resulting in cell dysfunctions, especially synoviocyte dysfunction. We revealed that the expression of osteopontin (OPN), which has been reported to regulate expression of various inflammatory factors associating with the pathogenesis of OA includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 42 publications
6
66
0
Order By: Relevance
“…Variations of the expression levels of lncRNAs have been association with OA (Liu et al, ). In our study, NEAT1 was significantly upregulated in OA cartilage tissue and chondrocytes, which was consistent with a previous report (Wang et al, ). NEAT1 was also found to play an essential role in the innate immune response (Imamura et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Variations of the expression levels of lncRNAs have been association with OA (Liu et al, ). In our study, NEAT1 was significantly upregulated in OA cartilage tissue and chondrocytes, which was consistent with a previous report (Wang et al, ). NEAT1 was also found to play an essential role in the innate immune response (Imamura et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Cytokines associated with inflammation, such as proteoglycans (PGs), IL‐1β, and TNF‐α, play a crucial role in the progression of OA (Caron et al, ). A previous study indicated that chondrocyte apoptosis played an important role in OA progression, and therapeutic agents that inhibit apoptosis of chondrocytes may effectively prevent OA progression (Wang et al, ). We, therefore, suggest that miR‐193a‐3p may serve as a therapeutic target for OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, lncRNA NEAT1 can modulate MMP13 expression by sponging miR-579 in vitro. Interesting, a relevant reported that lncRNA NEAT1 knockdown could reduce the MMP13 expression in osteoarthritis [37]. Accordingly, our study testified that lncRNA NEAT1 upregulated MMP13, the target gene of miR-579, further leading to abnormal proliferation, invasion and EMT of OS cells.…”
Section: Discussionmentioning
confidence: 53%
“…The study revealed that OPN could be classified as Thl cytokines, which could promote the synthesis of tumor necrosis factor (TNF)-α and IL-12 TNF, and inhibit the expression of IL-10 [8]. A recent study revealed that it can regulate expression of various inflammatory factors associating with the pathogenesis of OA including matrix metalloprotease 13, IL-6, and IL-8 [31]. OPN in OA patients highly expressed in cartilage and SF, and damage extent to knee was associated with OPN expression levels [32].…”
Section: Discussionmentioning
confidence: 99%